2017
DOI: 10.1515/abcsb-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

The First Evidence of a Host-to-Parasite Mitochondrial Gene Transfer in Orobanchaceae

Abstract: Several parasitic plants are known to have acquired mitochondrial genes via a horizontal transfer from their hosts. However, mitochondrial gene transfer in this direction has not yet been found in the parasite-rich family Orobanchaceae. Based on a phylogenetic analysis of the mitochondrial atp6 gene in selected species of Orobanche s.l., we provide evidence of a host-to-parasite transfer of this gene in O. coerulescens, which is a Eurasiatic species that parasitises Artemisia (Asteraceae). We did not find the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…(Asteraceae). Moreover, our data suggest the occurrence of a second HGT event from Asteraceae to Phelipanche, and confirm that the HGT from hosts to parasites influences mitochondrial genome evolution in the latter (Kwolek et al, 2017).…”
Section: Host Rangesupporting
confidence: 78%
See 2 more Smart Citations
“…(Asteraceae). Moreover, our data suggest the occurrence of a second HGT event from Asteraceae to Phelipanche, and confirm that the HGT from hosts to parasites influences mitochondrial genome evolution in the latter (Kwolek et al, 2017).…”
Section: Host Rangesupporting
confidence: 78%
“…It seems that the Orobanche and Phelipanche in the whole range definitely most frequently parasitize species of the Asteraceae family, which is also confirmed by the present study, as well as by data from the western hemisphere (Schneider et al, 2016) and western Asia (Piwowarczyk unpublished). In addition, in our recent work (Kwolek et al, 2017), we demonstrated a host-to-parasite horizontal transfer (HGT) of the mitochondrial atp6 gene in euroasiatic O. coerulescens, which parasitizes Artemisia sp. (Asteraceae).…”
Section: Host Rangementioning
confidence: 93%
See 1 more Smart Citation
“…The complete mitochondrial genome of Orobanchaceae, Castilleja paramensis has been reported [ 23 ], and Zavas et al [ 24 ] reported the mitochondrial genes of two Lathraea species. Genes of the Orobanchaceae plastome and mitogenome, such as atp1 [ 25 ], rpoC2 [ 26 ], atp6 [ 27 ], and nad1 [ 28 ], exhibit several transfers between Orobanchaceae and angiosperms.…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of putative HGT events have been identified across the Orobanchaceae, and many more in other lineages of parasitic angiosperms. However, only rarely are species and gene trees of both parasite and host lineages known with sufficient precision to draw inferences about molecular evolution, historical ecology and historical biogeography, for example the sustained host -parasite association between A. epigalium and its host Galium [10,14,16,45].…”
Section: Discussionmentioning
confidence: 99%